Implementation of the Partnering of the Faculty of Economics, UIN Malang with Madrasah Aliyah (MA) At-Taufiq Bogem Jombang in Increasing the Interest of Santri/Wati in Entrepreneurship - Wardana, Guntur; Hasibuan, Lempang (Jurnal Pengabdian Masyarakat Bestari, 2024)
The aim of community service carried out by the Faculty of Economics at UIN Malang with the At-Taufiq Islamic Boarding School is; 1) to find out the results of the implementation of the Faculty of Economics UIN Malang partnership with the At-Taufiq Islamic Boarding School on the interest of santri and female students in entrepreneurship; 2) To find out what factors become obstacles in entrepreneurship. The community service activities the Faculty of Economics at UIN Maulana Malik Ibrahim Malang carry out are seminars, interactive dialogues, and face-to-face group discussions. The number of participants who attended were 40 female students from the second and third grades of the Social Sciences Department Madrasah Aliyah. The results of this community service are; 1) To increase students' interest in entrepreneurship, this can be done by increasing the knowledge of students and female students related to the world of entrepreneurship; 2) To increase the motivation of santri and female students, provide material with displays in the form of pictures of someone successful in entrepreneurship as well as support from ustazd and ustazdah to the students.